Analysis of Gold Investment in Islamic Banking: Quantitative Simulation of Gold Farming - Sulistyowati Sulistyowati (Jurnal Ilmu Manajemen & Ekonomika, 2016)
This research analyzes gold investment in Islamic banking: quantitative simulation of gold farming. It uses secondary data, which are qardh financing for gold pawning, gold price per troy ounce per USD also rupiah exchange rate per USD and using quantitative simulation technique with mathematics method. There are several fundings from this research. Firstly, gold farming practices can cause losses, especially in lag four. It is caused by world gold prices fluctuations and the volatility of the rupiah exchange rate. Secondly, the amount of losses and profits every month and year is different in each lag execution among lag 1, lag 2, lag 3 and lag 4 months. Thirdly, a comparison result shows that frequency of losses and profits each year during simulation period causes difference final values of losses and profits. Based on simulation in this research, there are several things determining gold farming practices. They are gold value, Financing to Value (FTV) ratio, lag and the amount of pawned gold. So, it must be regulated or restricted by the regulator to prevent the customer doing gold farming practices in Islamic banks.